Farming structures, water and institutions in the Canary Islands - Alejandro González Morales, Miguel Suárez Bosa (Africana Studia, 2020)
In the archipelagos of the Atlantic Macaronesia, including the Canary Islands, water is a scarce resource. The regulation of its use and management led to a cultural heritage (form of distribution measured in dulas) characteristic institutions (heredamientos), which, in many cases, could be traced back to the places of origin of the conquerors, i.e. the Iberian Peninsula. This article discusses the institutions that have been developed in the Canaries to manage water use. Water was such a fundamental element in agricultural structures that initially, in the years after the conquest, ownership of water and land were practically synonymous. Using institutional and developmental theories, we analyze the evolution of water management from the early stage (15th to 16th centuries), when water was associated with land ownership. Eventually, later possession of both were separated, the heredamientos or irrigation communities formed parallel groups which give way to so-called water communities in the 19th century. In this system, property is private, gradually leading to a water market. Finally, a section devoted to analyzing conflicts caused by this privatization process. Keywords: water, institutions, heredamientos, water community, water market, water confl icts.